Bloom Taxonomy Based-Flipped Learning for the Teaching of English Speaking at Indonesian Higher Education Context - M. Junaidi Marzuki (Universitas Islam Negeri (UIN) Mataram, 2020)
This article provides practical application of employing flipped learning based bloom taxonomy theory in teaching English speaking at higher education. Flipped classroom/learning is defined as learning model in which content attainment is shifted forward to outside of class, then followed by instructor-facilitated concept application activities in class, while Bloom Taxonomy is set of learning framework used to classify the learning outcomes and objectives. To implement these two concepts, TED talks is used as the main teaching and learning material. Both strengths and weaknesses are analyzed for teachers’ consideration to implement this teaching model